A case of ossifying fibroma arising at the inferior border of the zygomatic arch - KOMAKI, Kanji; KIMURA, Yoshihiro; HASEGAWA, Shogo; OKUMURA, Yoshihide (Japanese Journal of Oral and Maxillofacial Surgery, 2008)
We describe a case of ossifying fibroma arising at the inferior border of the left zygomatic arch. A 22-year-old woman presented with a swelling and pain in her left cheek. A bony hard mass was found in the diffuseswelling of the cheek, adjacent to the zygomatic arch. CT imaging showed a bony, dense lesion in the left zygomaticimassetericregion. Interposition of soft tissue between the bony tumor and the zygomatic arch was recognized.Under a diagnosis of a benign bony tumor, the tumor was enucleated with the patient under general anesthesia.The histopathological diagnosis was an ossifying fibroma. An ossifying fibroma arising at the inferior borderof the zygomatic arch has not been reported previously, and the origin of the tumor is unclear. The patient hasremained relapse free for more than 2 years after the operation.